Hubungan Kompetensi Ibu, Aktivitas Fisik, dan Konsumsi Junk Food dengan Kejadian Obesitas pada Balita - Winarsi Pricilya Molintao; Suhendar Sulaeman; Nyimas Heny Purwanti (Journal of Telenursing (JOTING), 2019)
The purpose of this study is the relationship between maternal competence, physical activity, and consumption of junk food with the incidence of obesity in children under five in the work area of the Shoulder Health Center, Malalayang District, Manado City. This research is an explanatory research (Explanatory Research). The results showed that the value of physical activity with junk food was 0.000, physical activity with obesity was 0.016, competence of mothers with physical activity was 0.000, competence of mothers with junk food consumption was 0.011, competence of mothers with obesity was 0.072 and consumption of junk food with obesity was 0.0132. In conclusion, there is no relationship between maternal competence and obesity with a p value of 0.072. In conclusion, there is a relationship between physical activity and junk food consumption, there is a relationship between physical activity and obesity, there is a relationship between maternal competence and physical activity, there is a relationship between maternal competence and consumption of junk food. Keywords: Physical Activity, Maternal Competence, Junk Food Consumption, Obesity